2020
DOI: 10.1155/2020/9689312
|View full text |Cite
|
Sign up to set email alerts
|

DNA Primase Subunit 1 Expression in Hepatocellular Carcinoma and Its Clinical Implication

Abstract: DNA Primase Subunit 1 (PRIM1) is crucial for cancer development and progression. However, there remains a lack of comprehension concerning the clinical implication of PRIM1 in HCC. Here, aberrant expression of PRIM1 was identified in HCC according to available databases. The prognostic value of PRIM1 in patients presenting with HCC was further assessed based on TCGA data. Gene set enrichment analysis (GSEA) was subsequently conducted to investigate the potential function of PRIM1. Additionally, the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…PRIM1, as a new oncogene, was first found to be amplified in osteosarcoma [25] . At present, increasing evidence has shown that PRIM1 acts as an oncogene that enhances the aggressive behaviors of cancer cells, including cervical cancer [26] , hepatocellular carcinoma [27] , and colorectal cancer [28] , similar to our results. In breast cancer, silencing PRIM1 inhibits cell cycle progression and DNA damage by inactivating the G2/M cell cycle checkpoint [5] .…”
Section: Discussionsupporting
confidence: 92%
“…PRIM1, as a new oncogene, was first found to be amplified in osteosarcoma [25] . At present, increasing evidence has shown that PRIM1 acts as an oncogene that enhances the aggressive behaviors of cancer cells, including cervical cancer [26] , hepatocellular carcinoma [27] , and colorectal cancer [28] , similar to our results. In breast cancer, silencing PRIM1 inhibits cell cycle progression and DNA damage by inactivating the G2/M cell cycle checkpoint [5] .…”
Section: Discussionsupporting
confidence: 92%